15x^2+20x+[-6]x-8
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^6-6x^5+15x^4-20x^3+15x^2-6x+1=0\)
\(\Leftrightarrow x^6-x^5-5x^5+5x^4+10x^4-10x^3-10x^3+10x^2+5x^2-5x-x+1=0\)
\(\Leftrightarrow x^5\left(x-1\right)-5x^4\left(x-1\right)+10x^3\left(x-1\right)-10x^2\left(x-1\right)+5x\left(x-1\right)-\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^5-5x^4+10x^3-10x^2+5x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left[x^5-x^4-4x^4+4x^3+6x^3-6x^2-4x^2+4x+x-1\right]=0\)
\(\Leftrightarrow\left(x-1\right)\left[x^4\left(x-1\right)-4x^3\left(x-1\right)+6x^2\left(x-1\right)-4x\left(x-1\right)+x-1\right]=0\)
\(\Leftrightarrow\left(x-1\right)^2\left[x^4-4x^3+6x^2-4x+1\right]=0\)
\(\Leftrightarrow\left(x-1\right)^2\left[x^4-x^3-3x^3+3x^2+3x^2-3x-x+1\right]=0\)
\(\Leftrightarrow\left(x-1\right)^3\left[x^3-3x^2+3x-1\right]=0\)
\(\Leftrightarrow\left(x-1\right)^3\left[x^3-x^2-2x^2+2x+x-1\right]=0\)
\(\Leftrightarrow\left(x-1\right)^4\left[x^2-2x+1\right]=0\Leftrightarrow\left(x-1\right)^6=0\Leftrightarrow x=1\)
a. = \(6x^2+3x+12x+6=3x\left(2x+1\right)+6\left(2x+1\right)=\left(2x+1\right)\left(3x+6\right)=3\left(2x+1\right)\left(x+2\right)\)
b. \(=6x^2-3x-12x+6=3x\left(2x-1\right)-6\left(2x-1\right)=3\left(2x-1\right)\left(x-2\right)\)
c. \(=6x^2+2x+18x+6=2x\left(3x+1\right)+6\left(3x+1\right)=\left(2x+6\right)\left(3x+1\right)=2\left(x+3\right)\left(3x+1\right)\)
d. \(=6x^2-2x-18x+6=2x\left(3x-1\right)-6\left(3x-1\right)=2\left(x-3\right)\left(3x-1\right)\)
(+) 6x^2 + 15x + 6 = 6x^2 + 12x + 3x + 6
= 6x ( x+ 2 ) + 3 ( x + 2)
= ( 6x + 3) ( x + 2 )
= 3 (2 x + 1 ) ( x + 2)
(+) 6x^2 - 15x + 6 = 6x^2 - 3x - 12x + 6
= 3x( 2x - 1 ) - 6 ( 2x - 1 )
= ( 3 x - 6 )( 2x - 1)
= 3 ( x- 2 ) (2x- 1)
a: \(=\left(x+2\right)\left(x+3\right)\left(x-7\right)\left(x-8\right)-144\)
\(=\left(x^2-5x-14\right)\left(x^2-5x-24\right)-144\)
\(=\left(x^2-5x\right)^2-38\left(x^2-5x\right)+192\)
\(=\left(x^2-5x\right)^2-32\left(x^2-5x\right)-6\left(x^2-5x\right)+192\)
\(=\left(x^2-5x-32\right)\left(x^2-5x-6\right)\)
\(=\left(x^2-5x-32\right)\left(x-6\right)\left(x+1\right)\)
b: \(=\left(12x^2-12xy+3y^2\right)-20x+10y+8\)
\(=\left[3\left(2x-y\right)^2\right]-10\left(2x-y\right)+8\)
\(=3\left(2x-y\right)^2-4\left(2x-y\right)-6\left(2x-y\right)+8\)
\(=\left(2x-y\right)\left(6x-3y-4\right)-2\left(6x-3y-4\right)\)
\(=\left(6x-3y-4\right)\left(2x-y-2\right)\)
\(5x\left(x-2\right)-3\left(x-1\right)=20x^2-15x\left(2x+1\right)-24\)
\(\Rightarrow5x^2-10x-3x+3=20x^2-30x^2-15x-24\)
\(\Rightarrow5x^2-13x+3=-10x^2-15x-24\)
\(\Rightarrow5x^2+10x^2-13x+15x+3+24=0\)
\(\Rightarrow15x^2+2x+27=0\)
Ta có:
\(\Delta=2^2-4\cdot15\cdot27==-1616< 0\)
Nên pt vô nghiệm
\(5x\left(x-2\right)-3\left(x-1\right)=20x^2-15x\left(2x+1\right)-24\\ \Leftrightarrow5x^2-10x-3x+3=20x^2-30x^2-15x-24\\ \Leftrightarrow5x^2-20x^2+30x^2-10x-3x+15x+3+24=0\\ \Leftrightarrow15x^2+2x+27=0\\ \Leftrightarrow15x^2-2.x.\sqrt{15}+\dfrac{2}{15}+\dfrac{403}{15}=0\\ \Leftrightarrow\left(\sqrt{15}x+\dfrac{\sqrt{30}}{15}\right)^2+\dfrac{403}{15}=0\left(Vô.lí\right)\\ Vậy:Không.có.x.thoả\)
\(a,\dfrac{10x^3y^2}{20xy^5}=\dfrac{x^2}{2y^3}\\ b,\dfrac{15\left(x+5\right)^2}{20x\left(x+5\right)}=\dfrac{3\left(x+5\right)}{4x}\)
a) \(\dfrac{x^2}{2y^3}\)
b) \(\dfrac{3\left(x+5\right)}{4}\)=\(\dfrac{3x+15}{4}\)
`C(x) - D(x)=(7x^3+21+3x^2-15x)-(-3x^3 + 3x - 9)`
`= 7x^3+21+3x^2-15x+3x^3 - 3x + 9`
`= (7x^3+3x^3)+3x^2+(-15x-3x)+(21+9)`
`= 10x^3+3x^2-18x+30`
Hệ số cao nhất: `10`
`C(x)+D(x)=(7x^3+21+3x^2-15x)+(-3x^3 + 3x - 9)`
`= 7x^3+21+3x^2-15x-3x^3 + 3x - 9`
`= (7x^3-3x^3)+3x^2+(-15x+3x)+(21-9)`
`= 4x^3+3x^2-12x+12`
Hệ số cao nhất: `4`
`E(x)-F(x) = (16x^3 + 4 + 3x) - (-8 + 20x - 16x)`
`= 16x^3 + 4 + 3x +8 - 20x + 16x`
`= 16x^3+ (3x-20x+16x) +(4+8)`
`= 16x^3-x+12`
Hệ số cao nhất: `16`
`E(x)+F(x)=(16x^3 + 4 + 3x) + (-8 + 20x - 16x)`
`= 16x^3 + 4 + 3x- 8 + 20x - 16x`
`= 16x^3 +(3x+20x-16x)+(4-8)`
`= 16x^3+7x-4`
Hệ số cao nhất: `16`